Investigating thermal physiology as a tool to improve the release efficacy of insect biological control agents - Griffith, Tamzin Camilla (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2018)
Biological control is commonly used for the control of invasive aquatic weeds, which often involves the release of multiple host-specific agents. Releasing multiple agents has inherent safety concerns as the introduction of each new agent is associated with risks, but is often required to improve control where establishment is limited. Climatic incompatibility between the agent's thermal physiology and its introduced range often causes agents to fail to establish. However, it has been suggested that the thermal physiology of insects is plastic. Therefore, the potential to manipulate their thermal physiologies before releasing them into the field needs to be explored; reducing the need to release additional agents, thereby ensuring the safety of biological control. This thesis therefore aimed to firstly, determine whether season and locality influenced the thermal physiology of two field populations of a water hyacinth (Eichhornia crassipes) control agent, the mirid Eccritotarsus catarinensis; one collected from the hottest establishment site, and one collected from the coldest establishment site in South Africa. Their thermal physiology was significantly influenced by season and not by the sites' climate, suggesting their thermal physiology is plastic under field conditions. Secondly, the classical method of determining the lower critical thermal limit (CTmin), and a new respirometry method of determining this limit, compared the thermal physiology of two Eccritotarsus species reared in quarantine. Eccritotarsus catarinensis was significantly more cold tolerant than the more recently released Eccritotarsus eichhorniae, despite similar maintenance conditions, and as such, was used to establish whether cold hardening under laboratory conditions was possible. Successfully cold hardened E. catarinensis had a significantly lower CTmin compared to the field cold acclimated population, suggesting that cold hardening of agents could be conducted before release to improve their cold tolerance and increase their chances of establishment, allowing for further adaptation to colder climates in the field to occur. Increasing establishment of the most effective agents will decrease the number of agents needed in a biological control programme, thus encouraging a more parsimonious approach to biological control.
Keywords: Aquatic weeds -- Biological control; Water hyacinth -- Biological control; Insects -- Physiology; Miridae -- Effect of low temperatures on; Cold adaptation; Insects as biological pest control agents; Eccritotarsus catarinensis